Cerebral cortex and respiratory muscles perfusion during spontaneous breathing attempts in ventilated patients and its relation to weaning outcomes: a protocol for a prospective observational study. Issue 10 (31st October 2019) - Louvaris, Zafeiris; Van Hollebeke, Marine; Dhaenens, Alexander; Vanhemelen, Maarten; Meersseman, Philippe; Wauters, Joost; Gosselink, Rik; Wilmer, Alexander; Langer, Daniel; Hermans, Greet
Abstract : Introduction: In addition to the well-documented factors that contribute to weaning failure, increased energy demands of the respiratory muscles during spontaneous breathing trials (SBTs) might not be met by sufficient increases in energy supplies. This discrepancy may deprive blood and oxygen of other tissues. In this context, restrictions in perfusion of splanchnic organs and non-working muscles during SBT have been associated with weaning failure. However, alterations in perfusion of the brain during the weaning process are less well understood. Objective and hypothesis: To investigate whether cerebral cortex perfusion evolves differentially during the transition from mechanical ventilation (MV) to spontaneous breathing between patients failing or succeeding the SBT. We hypothesise that patients failing the SBT will exhibit reduced cerebral cortex perfusion during the transition from MV to spontaneous breathing as compared with patients succeeding the SBT. Methods and analysis: This single-centre, prospective, observational study will be conducted in a medical Intensive Care unit of University Hospital Leuven, Belgium in ready to wean patients. Blood flow index in the cerebral cortex (prefrontal area), inspiratory (scalene) and expiratory muscle (upper rectus abdominis) and a non-working muscle (thenar eminence) will be simultaneously assessed by near-infrared spectroscopy (NIRS) using the tracer indocyanine green dye. Measurements will be performed on the same day during MV and during SBT. NIRS-derived tissue oxygenation index and cardiac output (by pulse contour analyses) will be recorded continuously. Twenty patients failing an SBT are estimated to be sufficient for detecting a significant difference in the change of cerebral cortex perfusion from MV to SBT (primary outcome) between SBT failure and success patients. Ethics and dissemination: Ethics approval was obtained from the local ethical committee (Ethische Commissie Onderzoek UZ/KU Leuven protocol ID: S60516). Results from this study will be presented at scientific meetings and congresses and published in peer-reviewed journals. Trial registration number: NCT03240263; Pre-results .